2011
DOI: 10.4049/jimmunol.1100790
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 Inflammasome Contributes to Brain Injury in Pneumococcal Meningitis and Is Activated through ATP-Dependent Lysosomal Cathepsin B Release

Abstract: Streptococcus pneumoniae meningitis causes brain damage through inflammation-related pathways whose identity and mechanisms of action are yet unclear. We previously identified caspase-1, which activates precursor IL-1 type cytokines, as a central mediator of inflammation in pneumococcal meningitis. In this study, we demonstrate that lack of the inflammasome components ASC or NLRP3 that are centrally involved in caspase-1 activation decreases scores of clinical and histological disease severity as well as brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
166
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 72 publications
(100 reference statements)
6
166
1
2
Order By: Relevance
“…We found that IFN-g production in the brain following S. pneumoniae inoculation was dependent upon ASC, which is a key adaptor molecule for multiple inflammasomes. Our data are consistent with reports that argue that the pneumococcal toxin pneumolysin is recognized via ASC-dependent inflammasomes, in particular those containing NLRP3 and/or AIM2 (16)(17)(18)(19). Recently, IFN-g production secondary to inflammasome-mediated IL-18 activation was reported in response to flagellated bacteria (77) or to S. pneumoniae during lung infection (18).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We found that IFN-g production in the brain following S. pneumoniae inoculation was dependent upon ASC, which is a key adaptor molecule for multiple inflammasomes. Our data are consistent with reports that argue that the pneumococcal toxin pneumolysin is recognized via ASC-dependent inflammasomes, in particular those containing NLRP3 and/or AIM2 (16)(17)(18)(19). Recently, IFN-g production secondary to inflammasome-mediated IL-18 activation was reported in response to flagellated bacteria (77) or to S. pneumoniae during lung infection (18).…”
Section: Discussionsupporting
confidence: 81%
“…However, the clear dependence of IFN-g upon ASC and IL-18 shown in this study indicates that IL-18 production secondary to inflammasome formation is the dominant pathway of IFN-g production during pneumococcal infection in the brain. This is of particular relevance, because a recent study showed that the NLRP3 inflammasome contributes to pathology in pneumococcal meningitis through production of IL-1b and IL-18, and this was associated with diminished leukocyte recruitment in NLRP3-deficient animals (17). Our data extend these findings to show that inflammasome-dependent pathology is, at least in large part, dependent upon IL-18-mediated induction of IFN-g rather than through direct effects of IL-1b and IL-18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence indicates that NLRP3 inflammasomes play a significant role in the recognition of and response to bacterial infection. Although there is no direct evidence for the interaction of bacterial ligands with NLRP3, a variety of pathogenic bacteria including Staphylococcus aureus (Craven et al 2009;Holzinger et al 2012;Kebaier et al 2012;Maher et al 2013;McGilligan et al 2013;Muñoz-Planillo et al 2009), Streptococcus pneumoniae (Hoegen et al 2011;McNeela et al 2010;Witzenrath et al 2011) and Listeria monocytogenes (Meixenberger et al 2010) have been Arch. Immunol.…”
Section: Il-1b/il-18 Processing and Pyroptosis Inductionmentioning
confidence: 99%
“…1 Caspase-1 activation and interleukin-1 (IL-1) release have a central role in many disorders with an inflammatory component, 2 which comprises different diseases of the central nervous system (CNS) such as multiple sclerosis, Alzheimer disease, meningitis, or stroke. [3][4][5][6][7][8] The potential molecular signals, which activate the inflammasomes in the CNS, have already been delineated in detail before. 8,9 Thus, this overview aims at a more global, system biologic view of the potential role of the inflammasomes in CNS diseases and accounts for recent discoveries in related research fields.…”
Section: Introductionmentioning
confidence: 99%